Influence of physical and chemical properties of soybean grains on drying process (Research, Society and Development, 2020)
Grain drying can be influenced by many factors and energetic knowledge of this process is essential. The objective was to evaluate the influence of soybean grain properties on drying kinetics and thermodynamic properties. Four soybean cultivars were studied through sphericity, circularity, volume, oil content, total protein and initial moisture in a completely randomized design. Drying was performed at temperatures of 40 and 60 °C, adjusting six mathematical models. By the statistical criteria different models were selected to the cultivars, which were used in the thermodynamic properties’ calculations. The cultivar C with lower volume presented higher drying rate and higher constant k, which presented lower activation energy 23.81 kJ mol-1. The thermodynamic properties of Gibbs enthalpy, entropy and free energy were mainly influenced by volume, being lower for cultivar C.